Ma’na al-Hub Fi Kitaab al-Hub fi al-Qur’an al-Karim bi Qalam M. Said Ramadhan al-Buthi Istinadan Ila al-Mandzur al-Siimiiya’iy li Roman Jakobson - Amrulloh, Ahmad Yasir; Arifandi, Fathoni (Afshaha: Jurnal Bahasa dan Sastra Arab, 2022)
Every human being planted by God since birth has a sense of  love in his heart. With this feeling, man will be overwhelmed with peace and tranquility. When he knows love, he will choose who should put love first, the father and the father, the acquaintance, or the opposite sex. Or even he chose himself for him to love her. Even in  this field,  man may sometimes forget to declare his love  for the one who instilled love in his heart. It’s Allah the Almighty  who instilled love and the Messenger (peace and blessings of Allaah be upon him) was the first to feel  this love and this love for man to love Allah. This paper will describe the meaning of love in the book of love in the  Holy Quran by Saeed Ramadan Alp and Fold. This paper is a qualitative and descriptive research. Preliminary data are derived from the book  "Love" in the Qur'an. The results of this study showed that the meaning of   Love in the Qur'an is honor and the glory God gave to the Son of Adam.  God's honor for people shaped  who  is love after following  the Prophet Muhammad as the recipient of the tablet. This love leads to  human beings  working  by submitting to the law   of God Almighty. Based on the point of view of Roman Jacobson's theory of semiotics, this paper produces six important elements: Thesender is Allah the Almighty, the recipient  The recipient is the Prophet Muhammad (peace and blessings of Allaah be upon him), the message  and symbols are the  verses that are revealed according to reality, and the context is the state or that surrounds the revelation of the verse, while the connection is when God spoke and his angels Gabriel transmitted  it to the Prophet Muhammad. كل إنسان زرعه الله منذ ولادته لديه شعور بالحب في قلبه. وبهذا الشعور، سيغمر الإنسان السلام والهدوء. عندما يعرف الحب، سيختار من يجب أن يضع الحب أولا، الوالد، أو معرفة، أو الجنس الآخر. أو حتى أنه اختار نفسه له ليحبها. حتى في هذا المجال قد ينسى الإنسان أحيانا أن يعلن حبه للذي أغرس الحب في قلبه. هو الله سبحانه وتعالى  الذي أغرس الحب والرسول صلى الله عليه وسلم  أول من أحس هذا الحب وبهذا الحب على الإنسان أن يحب الله . ستصف هذه الورقة معنى الحب في كتاب الحب في القرآن الكريم بقلم سعيد رمضان البوطي. هذه الورقة هي بحث نوعي وصفي. البيانات الأولية مستمدة من كتاب "الحب" في القرآن. أظهرت نتائج هذه الدراسة أن معنى الحب في القرآن هو التكريم والمجد أعطاهما الله لابن آدم. وشكل تكريم الله للناس من هو المحبة بعد الاتباع بالنبي محمد كمستلم للوحي. هذه المحبة تأدي إلى البشر العملين بالخضوع لشريعة الله عز وجل. استنادا إلى وجهة نظرية رومان جاكوبسون في السيميائية، تنتج هذه الورقة ستة عناصر مهمة، وهي: المرسل هو الله سبحانه وتعالى، المستلم والمتلقي هو النبي محمد صلى الله عليه وسلم، والرسالة والرموز هما الآيات المنزلة حسب الواقع، والسياق هو الحالة أو التي تحيط بنزول الآية، في حين أن الاتصال هو عندما كلم الله وينقله ملائكته جبريل إلى النبي محمد.